2021
DOI: 10.2139/ssrn.3776854
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Insurrection: Characterizing Collective Action Using Mobile Device Data

Abstract: We develop a novel approach for estimating spatially dispersed community-level participation in mass protest. This methodology is used to investigate factors associated with participation in the 'March to Save America' event in Washington, D.C. on January 6, 2021. This study combines granular location data from more than 40 million mobile devices with novel measures of community-level voting patterns, the location of organized hate groups, and the entire georeferenced digital archive of the social media platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…For instance, Twitter CEO Jack Dorsey has expressed concern about the popularity of "dunking" (i.e., mocking or denigrating one's enemies) on the platform (2). These concerns have become particularly relevant as social media rhetoric appears to have incited real-world violence, such as the recent storming of the US Capital (3). We sought to investigate whether out-group animosity was associated with increased virality on two of the largest social media platforms: Facebook and Twitter.…”
mentioning
confidence: 99%
“…For instance, Twitter CEO Jack Dorsey has expressed concern about the popularity of "dunking" (i.e., mocking or denigrating one's enemies) on the platform (2). These concerns have become particularly relevant as social media rhetoric appears to have incited real-world violence, such as the recent storming of the US Capital (3). We sought to investigate whether out-group animosity was associated with increased virality on two of the largest social media platforms: Facebook and Twitter.…”
mentioning
confidence: 99%
“…Based on nationally representative survey data, they found that alt-right supporters were more likely than both non-alt-right Trump voters and non-Trump voters to be higher in authoritarianism, biased against minority groups, supportive of white identitarian collective action, and distrustful of mainstream media. Using a mixture of mobile location data, public social media metadata, and precinct-level election data from the 2016 presidential election, Van Dijcke and Wright (2021) found that increased political isolation, proximity to local chapters of extremist groups (e.g. the Proud Boys), and engagement with alternative social media sites like Parler were associated with active participation in the 6th January insurrection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, other research argues that using social media has little effect on users’ opinions and behavior (e.g., Foos et al 2020; Schumann et al 2021; Theocharis and Lowe 2016), and that individuals’ existing attitudes drive their use of social media (Heiss and Matthes 2019; Nordbrandt 2021). Moreover, much of the scholarship attributing offline mobilization to social media has limited scope, focusing on places with authoritarian regimes (e.g., Enikolopov, Makarin, and Petrova 2020; Steinert-Threlkeld 2017; Weidmann and Rød 2019) or large but rare protests, such as the 2015 Charlie Hebdo protests (Larson et al 2019) and the 2021 U.S. Capitol riot (Van Dijcke and Wright 2021).…”
mentioning
confidence: 99%